Strengthening Global Diversity Values through Profil Pelajar Pancasila in Citizenship Education Learning - Thoriq Abdul Aziz; Aim Abdulkarim (Proceeding International Conference on Religion, Science and Education, 2023)
Indonesia is a country that has diversity in various aspects, which is stated in the motto Bhinneka Tunggal Ika as the country statement. The implementation of diversity in Indonesia had been found in various aspects, one of which is carried out through learning activities in school units. Pancasila and Citizenship Education is a field of study examining the strengthening of diversity character education to create students who understand the national identity of the country. Civics learning in education units currently uses Kurikulum Merdeka which integrated learning based on the Profil Pelajar Pancasila. This research uses a literature study method by examining 30 (thirty) relevant journal articles about Profil Pelajar Pancasila and the global diversity aspect. The results obtained are 1) Citizenship education learning based on Profil Pelajar Pancasila integrates global diversity values as part of the dimension taught 2) aspects of global diversity that emerge are intercultural communication, tolerance, and an attitude of respect for others 3) integration of global diversity values in citizenship education by using the Profil Pelajar Pancasila in that curriculum is one way to strengthen character global diversity of students 4) Strengthening the character of global diversity is seen like independent curriculum learning activities through differentiated learning values in schools.